(untitled) (New York, 2017)
Handbook of Research in Second Language Teaching and Learning, like Volumes I and II, is a comprehensive, state-of-the-art overview of current research into social contexts of second language (L2)/foreign language (FL) teaching and learning; language policy; curriculum; types of instruction; incremental language skills such as listening, speaking, reading, writing, vocabulary, and grammar; international communication; pragmatics; assessment and testing. It differs from earlier volumes in its main purpose―to provide a more in-depth discussion and detailed focus on the development of the essential language skills required for any type of communication: speaking, listening, reading, vocabulary, grammar, and writing.
Keywords: Tiếng Anh,English language; Học tập và giảng dạy,Người nước ngoaig,Study and teaching,Foreign speakers